Power profiling, workload characteristics, and race performance of U23 and professional cyclists during the multistage race tour of the alps - Leo, P.; Spragg, J.; Mujika, I.; Giorgi, A.; Lorang, D.; Simon, D.; Lawley, J. S. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The aim of this study was to compare the power profile, internal and external workloads, and racing performance between U23 and professional cyclists and between varying rider types across 2 editions of a professional multistage race.